SOSIALISASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN, RISET DAN TEKNOLOGI RI NO. 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI - Laxmi, Laxmi; Yusran, Sartiah; Hidayat, Sabrina; Mokodompit, Eliyanti Agus; Herik, Eva; Akifah, Akifah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Identification of the problem found is that the Regulation of the Minister of Education and Culture, Research and Technology of the Republic of Indonesia has not been socialized. 30 of 2021. The objectives of this activity are: first, to prevent sexual violence related to the implementation of the tridharma on or off campus (CHAPTER I ARTICLE 2 PERMENDIKBUD RISTEK RI No. 30 of 2021). Second, foster a humane, dignified, inclusive, collaborative and non-violent campus life among students, educators, educational staff, and campus residents in tertiary institutions. The results of the discussion are that through the process of this community service activity participants can express their hopes and concerns about this activity related to the Prevention and Handling of Sexual Violence, so that this can become a strength in subsequent forums/activities in preventing acts of sexual violence so that there are no more repeated cases in the scope education